Invasive Bacillus cereus Infection in a Renal Transplant Patient: A Case Report and Review - Susan John; John Neary; Christine H Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacillus cereus is a common cause of gastrointestinal diseases. The majority of individuals with B cereus-related food poisoning recover without any specific treatment. It can, however, rarely cause invasive disease in immunocompromised patients.